Investigation of Phase Transitions and Properties of Aluminum Oxides Prepared by Oxidation of Al/AlN Nanopowder; AIP Conference Proceedings; Vol. 1783 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2016 - Kazantsev S. O. Sergey Olegovich (2016, 2016)
Title screen